2016
DOI: 10.1177/1947603516675915
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intra-articular Injection of Hyaluronic Acid and N-Acetyl Cysteine in the Treatment of Knee Osteoarthritis: A Pilot Study

Abstract: Objective To compare the relative effectiveness of intra-articular N-acetyl cysteine (NAC) and hyaluronic acid (HA) on pain, function and cartilage degradation markers in patients with mild to moderate knee osteoarthritis (OA). Design We prospectively conducted a clinical trial with 20 patients having a diagnosis of Kellgren-Lawrence grade 2-3 knee OA, and randomly allocated to the HA or NAC groups. Groups were matched on age, sex, and body mass index. Injections of 3-mL HA (Hylan G-F 20) or 3-mL NAC (Asist am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 40 publications
0
22
0
5
Order By: Relevance
“…Moreover, NAC reduced cartilage degradation markers and exhibited comparable beneficial effects to hyaluronic acid after a single i.a. injection in patients suffering from mild to moderate knee OA [13].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NAC reduced cartilage degradation markers and exhibited comparable beneficial effects to hyaluronic acid after a single i.a. injection in patients suffering from mild to moderate knee OA [13].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 57 included data for IA HA mono-injection 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70. At the end, 28 studies were included,43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70 whereas 29 studies were removed for 1 or several of the following reasons:Two studies were in combination with surgery: anterior cruc...…”
Section: Resultsmentioning
confidence: 99%
“…Eight with experimental regimens from a multi-injection product: single-shot,26, 27, 28 or large shot grouping several syringes,29, 30, 31 or smaller shot, 32 or retreatment 33 ;…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the hypothesis that NAC retards the inflammation process, long-term treatment with oral NAC was found to cause no significant reduction in the activity of neutrophilic inflammatory biomarkers in patients with cystic fibrosis [25]. However, in a pilot study, Ozcamdalli compared the efficacies between intra-articular injections of HA or NAC in the treatment of knee OA and revealed that NAC had outcomes comparable to those of HA in terms of pain and function scales, but biomarkers within or between groups exhibited equivocal results [10].…”
Section: Discussionmentioning
confidence: 99%
“…According to experimental and tissue culture studies, NAC is effective in clearing free-oxygen radicals, slowing the cartilage degradation process, reducing synovial inflammation, and reducing pain. In addition, one recent study confirmed that NAC use in patients with knee OA yielded more effective pain relief and better functional outcomes compared with intra-articular injection of HA [ 10 ]. However, few studies have examined the therapeutic effects of NAC on OA.…”
Section: Introductionmentioning
confidence: 99%